COVID-19 return to training. Guidance on safe return to training for athletes - NSCA Taskforce (National Strength and Conditioning Association, 2020)
COVID-19: Training landscape and challenges Minimizing risk: managing schedules and teams training sessions Facility & equipment: cleaning & sanitation procedures Training safety: risk factors following periods of inactivty Other important factors